Seed dormancy and germination in two wild genotypes of Sesbania of the southwest mangroves in India - Shreelalitha, S. J.; Sridhar, K. R.; Sukesh, S. (International Journal of Agricultural Technology, 2015)
Seed germination and vigour index of two wild legumes Sebania bispinosa and S. speciosa of the Nethravathi mangroves of Southwest India were evaluated. Seeds of S. bispinosa were more dormant compared to the seeds of S. speciosa. Among the physical treatments (soaking and elevation of temperature), soaking in distilled water (24 hr) resulted in highest seed germination as well as vigour index in both plant species. Among the chemical treatments (ethanol, sulfuric acid, thiourea, potassium nitrate and gibberelic acid), immersion in sulfuric acid (20 min) showed the highest seed germination and vigour index in S. bispinosa. In S. speciosa the highest germination and vigour index was seen by soaking in gibberellic acid (250 mg/l for 24 hr).